2010
DOI: 10.1038/nbt.1618
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic silencing of miR-10b inhibits metastasis in a mouse mammary tumor model

Abstract: MicroRNAs (miRNAs) are increasingly implicated in regulating metastasis. Despite progress in silencing miRNAs in normal tissues of rodents and non-human primates, the development of effective approaches for sequence-specific inhibition of miRNAs in fast-growing tumors remains a significant scientific and clinical challenge. Here we show that systemic treatment of tumor-bearing mice with miR-10b antagomirs – a class of chemically modified anti-miRNA oligonucleotides – suppresses breast cancer metastasis. Silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
545
2
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 720 publications
(581 citation statements)
references
References 45 publications
28
545
2
6
Order By: Relevance
“…The total bilirubin concentration was also slightly increased over normal limits in the anti-miR treatment group. Similar increases in hepatic enzymes and bilirubin have been reported as a result of antagomiR-10b treatment in a mouse mammary tumor model (Ma et al, 2010), despite differences in anti-miR administration and oligonucleotide conjugation. Although the total number of Kupffer cells was slightly increased in the control group, as described in Ma et al, 2010, we observed a significantly higher percentage of these cells per tumor volume (an index of the number and size of metastases) in the anti-miR-182-treated cohort (Supplementary Figures 5b and c).…”
Section: Targeting Liver Metastasis With Anti-mir-182supporting
confidence: 75%
See 1 more Smart Citation
“…The total bilirubin concentration was also slightly increased over normal limits in the anti-miR treatment group. Similar increases in hepatic enzymes and bilirubin have been reported as a result of antagomiR-10b treatment in a mouse mammary tumor model (Ma et al, 2010), despite differences in anti-miR administration and oligonucleotide conjugation. Although the total number of Kupffer cells was slightly increased in the control group, as described in Ma et al, 2010, we observed a significantly higher percentage of these cells per tumor volume (an index of the number and size of metastases) in the anti-miR-182-treated cohort (Supplementary Figures 5b and c).…”
Section: Targeting Liver Metastasis With Anti-mir-182supporting
confidence: 75%
“…As an example, anti-miR10b-mediated targeting of breast cancer lung metastases was successfully achieved by intravenous injection of cholesterolconjugated anti-miRs (Ma et al, 2010). Therapeutic silencing of miR-122 with locked nucleic acid-modified oligonucleotides led to a long-lasting suppression of HCV viremia and improved liver pathology (Lanford et al, 2010).…”
Section: Targeting Liver Metastasis With Anti-mir-182mentioning
confidence: 99%
“…Interestingly, the effect of mutations on AMO function did not track this way. Instead, mutations placed at the center of the AMOs (corresponding to bases 9-12 of the miRNA) and the 5¢-ends (bases [19][20][21][22][23] showed relatively little impact on AMO potency whereas mutations placed in the 3¢-end (bases 3-8) and off-center to the 5¢-side (bases [13][14][15][16][17][18] showed much greater effects. The 3¢-domain of the AMO pairs with the 5¢-end of the miRNA where the seed region is located; bases 2-8 are most critical for determining miRNA specificity.…”
Section: Specificitymentioning
confidence: 98%
“…Other groups using the antagomir design have also found it to be effective in vivo. For example, Thum et al 4 demonstrated a role for miR-21 in controlling mitogen-activated protein kinase signaling in fibroblasts using miR-21 antagomirs in a murine cardiac fibrosis model system and Ma et al 23 demonstrated a role for miR-10b in tumor metastasis using antagomirs and a murine mammary tumor model system. Krützfeldt 21 also tested 2¢OMe miR-122 AMOs having complete PS modification and these compounds did not show reductions in miR-122 levels.…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…The function of miRNAs may be deregulated in cancer in several manners, including miRNA gene mutation, deletion or promoter hypermethylation, but also as a consequence of mutations in their target sequences (Esquela‐Kerscher and Slack, 2006; Nana‐Sinkam and Croce, 2011; Palmero et al., 2011). Although attenuated expression of the miRNA transcriptome is frequently observed (Kumar et al., 2007; Lu et al., 2005), various miRNAs are overexpressed in specific tumors compared to their healthy tissue of origin (Ma et al., 2010a,b; Volinia et al., 2006), and thus are termed “oncomiRs”. Furthermore, the predicted targets for several cancer‐associated miRNAs include protein‐coding tumor suppressors and oncogenes, supporting a role for miRNAs in cancer pathogenesis (Esquela‐Kerscher and Slack, 2006; Nana‐Sinkam and Croce, 2011; Palmero et al., 2011).…”
Section: Addressing Tumor Heterogeneity and Complexitymentioning
confidence: 99%